Quality management : reconsidered for the digital economy - Beckford, John, 1958- (New York, NY : Routledge, 2022)
"Quality Management: Reconsidered for the Digital Economy continues to provide a one-stop-shop for anyone studying the theory and practice of quality management. Exploring the essentials of management theory and the work of the 'quality gurus' who have formed the foundation of current practice, this new edition builds upon the previous editions' unique critical perspective of quality. Key management practices are considered and extended, including lean thinking, systems methodologies, business process reengineering, organisational learning and intelligent organisations and service quality management. This edition plays particularly close attention throughout to the impact of the 4th Industrial Revolution on Quality Management, revisiting the meaning of 'quality' in an automated and data-driven world. Throughout, case studies have been rewritten including new examples from emerging economies, and practical tools incorporated to enhance learning and application. Replete with examples, vignettes and diagrams, this comprehensive textbook is ideal for those new to the field of quality management and for students on advanced undergraduate and postgraduate courses in Operations Management. Online resources include chapter-by-chapter PowerPoint slides and a test bank of questions"--
Previous edition title: Quality : a critical introduction.
OCLC-licensed vendor bibliographic record.
Keywords: Total quality management -- Case studies; Service industries -- Management -- Case studies; Manufacturing industries -- Management -- Case studies; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Project Management